GreenLight (532 nm) laser partial nephrectomy followed by suturing of collecting system without renal hilar clamping in porcine model - Eret, Viktor; Hora, Milan; Sýkora, Roman; Hes, Ondřej; Ürge, Tomáš; Klečka, Jiří; Matějovič, Martin (Urology, 2009)
OBJECTIVES: To assess the feasibility of partial nephrectomy (PN) without renal hilar clamping using the 80-W GreenLight (532 nm) laser with opening of the collecting system followed by its suture in a porcine model.
Keywords: financování organizované; Animals; krvácení při operaci; konstrikce; hodnocení rizik; Feasibility Studies; hemostatické techniky; výsledek terapie; sběrací ledvinové kanálky; Sus scrofa; Blood Loss, Surgical; Immunohistochemistry; Recovery of Function; ledvinná pánvička; Sensitivity and Specificity; prasata; Treatment Outcome; senzitivita a specificita; Risk Assessment; Constriction; Nephrectomy; imunohistochemie; Suture Techniques; obnova funkce; Financing, Organized; Lasers; studie proveditelnosti; jehlová biopsie; modely nemocí na zvířatech; Kidney Tubules, Collecting; Swine; Biopsy, Needle; lasery; Kidney Function Tests; Disease Models, Animal; Hemostatic Techniques; vyšetření funkce ledvin; šicí techniky; zvířata; Kidney Pelvis; laserová terapie; Laser Therapy; nefrektomie